Supply reduction policy against new psychoactive substances in China : policy framework and implementation - Zhao, Minqi (2019)
The global new psychoactive substances (NPS) phenomenon has been facilitated by the illicit supply thereof in China. In response, Chinese authorities updated laws and regulations, and engaged in law enforcement efforts at the national and international levels. However, what are the legal responses and how they function to reduce the illicit supply of NPS have rarely been addressed. This study aims to fill the policy gap by focusing on the design of the policy framework and the way of implementation. The study found that zero-tolerance and the state-centric policy mobilized social actors’ engagement involuntarily. In addition to the passive ethos, the competing regulatory power and incentives, and economic and political contexts appear to further limit the efficiencies of law enforcement. The study concludes that focusing on deficiencies that can be corrected while considering the economic and political contexts would benefit the efforts to reduce the supply of NPS